The THERAPEUTIC IMPORTANCE OF GUMS IN FOLK MEDICINE FROM EASTERN GHATS, ANDHRA PRADESH: Traditional uses of gums - VENKATA RATNAM K; TIRUPATI REDDY G; VENKATA RAJU RR (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of the present study is to collect ethnobotanical information of gums of medicinal plants from Eastern Ghats of Andhra Pradesh. Methods: Intensive ethnobotanical field trips were conducted in the forests of Eastern Ghats to collect firsthand information on therapeutic importance of gums used in folk medicine. Results: The present report deals with the therapeutic importance of gums in folk medicine used by local tribes inhabiting in and around the forests of Eastern Ghats of Andhra Pradesh. The results of the present study revealed that 21 crude drugs belong to 19 genera and 14 families of higher plants. The critical review of literature on crude drugs with reference to that of Eastern Ghats revealed that 13 crude drugs are hitherto not known to the science. 24 herbal formulations are commonly prepared by the local people to cure 14 human ailments. Out of 21 crude drugs reported in the present study, 10 crude drugs have pharmaceutical importance, namely drug delivery agents (Acacia), disintegrate in tablets (Sterculia), thickeners in oral liquids (Acacia and Mangifera), dilutents, binders, gelling agents in gels (Butea, Neem, and Moringa), and protective colloids in suspensions (Anogeissus) and bases in suppository. Conclusion: Natural gums of plant origin have multifarious pharmaceutical applications. In view of the potential crude drugs with promising therapeutic properties used by the tribal people, there is a need to take up the phytochemical and pharmacological investigations.